African political mobilisation in Brakpan in the 1950s - Sapire, Hilary Joan (My University, 1989)
With the notable exception of Tom Lodge's recent work, much of the literature which addresses itself to the turbulent decade of African politics of the 1950s focuses almost exclusively on formal political organisations and their national leaders. Rarely do the roles and consciousness of local political figures and the "led" or rank and file come into view. The foreground is invariably occupied by national middle class African figures planning, forming alliances, overhauling the structures of their organisations and directing mass activity. Beyond this phalanx, we can barely make out the blurred and somewhat undifferentiated feature of the urban masses. Occasionally their profiles are illuminated in a "flashpoint" of class conflict or their actions may momentarily be sighted in a flare-up of rioting during one of the major political campaigns of the decade. But all too rarely are these moments of resistance situated in their immediate terrain. This absence of sensitivity to the sociology and social history of urban African communities of the 1950s is especially glaring, as it was in this decade that urban Africans were subjected to unprecedented measures of social restructuring and social engineering with the implementation of apartheid. Similar criticisms can be levelled at the writings of Marxist scholars who are concerned with the social composition and changing ideological discourse of the major political organisation of the period, the ANC. Like the institutional historians, they fail to locate the growth of political organisations and the development of a mass-based politics within the changing sociological realties of South Africa's towns and ci ties, and thereby to probe their assumptions about the history of urban African societies and the class bases of political movements. The institutional focus has also meant that a variety of urban constituencies, idioms of protest, ideologies and forms of consciousness which fed into the overall mass political culture of the decade rarely surfaces, while the social groupings which were neither reflected in nor embraced by the ANC, remain invisible in most accounts. The crucial role that "dummy" or "collaborationist" institutions, such as the Location Advisory Board could, and sometimes did play in mobilising African communities around the ANC programmes, for example, has been little understood. Conversely, although much direct action occurred outside the scope of formal organisation, many urban constituencies in which the ANC failed to strike strong roots, have been obscured or ignored altogether. The history of urban squatter movements in the 1950s is thus almost unknown. Finally, the institutional bias of historians has meant that the immense regional variations in political cultures and styles of protest have not been explained and that the notoriously uneven responses to the ANC campaigns of the decade have not been adequately understood. This paper does not aim to provide a comprehensive corrective but it is concerned, through the Brakpan case to point to aspects of urban social history which may enhance our understanding of the complexity and variability of black political mobilisation in the 1950s. It emphasises the value of examining the local permutations in the unfolding of the huge processes of industrialisation and African urbanisation and in the municipal administration of African communities for understanding popular responses to political organisation in the decade. Thus, this paper demonstrates the laggard industrial growth in Brakpan, the delayed implementation of apartheid social engineering and the peculiarly harsh administration of "the native location" had crucial implications for the social nature of political organisation and for the modes of resistance and protest employed.
African Studies Seminar series. Paper presented March 1989
Keywords: Political participation. South Africa. Brakpan